Expenses Mastery: Thriving on Thrift for Sustainable Budgeting and Elevating Finnov - Lulaj, Enkeleda; Lulaj, Donjeta (Ekonomika, 2025)
The purpose of this study was to examine the relationships between factors influencing business expense management and their impact on mastering expenses in the context of fostering sustainable budgeting and financial innovation (Finnov). The research focused on identifying critical elements that contribute to expense optimization and financial sustainability within corporations. The study employed a quantitative research design using data collected from treasurers and financial managers of 200 corporations in the Western Balkan Countries between 2020 and 2023. Analytical methods, including exploratory factor analysis, reliability analysis, and multiple regression analysis, were used to explore the relationships between various factors and their impact on expense management practices systematically. The findings revealed significant statistical relationships between expense management practices and sustainable budgeting. Key factors such as transparency, timely reimbursement, and clear communication emerged as critical for optimizing expense management. Additionally, flexibility in financial processes, enhanced financial communication, and the integration of financial and business management performance were identified as drivers of financial sustainability and innovation. This study contributes novel insights into the interplay between expense management and financial innovation, emphasizing actionable strategies for achieving financial sustainability. The results provide valuable guidance for businesses aiming to refine their expense management frameworks, support sustainable budgeting, and foster innovation in financial practices.